Asymmetric Synthesis of 3,3-Disubstituted Isoindolinones Enabled by Organocatalytic Functionalization of Tertiary Alcohols - Wang, Jin-Long; Mao, Bin (Synthesis, 2022)
An enantioselective intramolecular heterocyclization with in situ generated 3-hydroxyisoindolinone-derived N-acyliminium ions has been successfully accomplished. In the presence of a catalytic amount of a chiral phosphoric acid, functionalized 3,3-disubstituted isoindolinones bearing N-acyl-N,O-acetal moieties were obtained with good yields and a high level of stereocontrol (up to 98:2 er). This efficient method proceeds under mild conditions and exhibits broad scope with respect to both 3-hydroxyisoindolinones and hydroxyl partners.
Keywords: N-acyliminium ion; chiral phosphoric acid; 3,3-disubstituted isoindolinones; N-acyl-N,O-acetal; enantioselective